Photoinactivation of bacterial and fungal planktonic/biofilm forms using the combination of a porphyrinic formulation with potassium iodide - Vieira, Cátia (2022)
Antimicrobial photodynamic therapy (aPDT) is a promising approach against multidrug-resistant microorganisms. In this work, we accessed the photodynamic efficiency of an affordable formulation composed of five cationic porphyrins (FORM) and its combined effect with potassium iodide (KI) on a large spectrum of microorganisms. For this purpose, the aPDT assays were conducted with FORM alone and FORM + KI on planktonic and biofilm forms of Gram(+) (Staphylococcus aureus) and Gram(−) (Escherichia coli) bacteria and of the yeast Candida albicans. The results obtained indicate that FORM, at low concentrations (0.5–5.0 μM), had an efficient photodynamic action on the planktonic forms of E. coli, S. aureus, and C. albicans. Moreover, the combination of FORM with KI improved the photodynamic action of this PS, promoting microbial inactivation with lower PS concentrations and treatment time. The combination of FORM + KI was also extremely efficient in the destruction of bacterial and fungal biofilms. This outstanding effect may be due to the action of longer-lived iodine reactive species produced by the reaction of KI with the ROS generated by FORM during the aPDT treatment.